Modelisation Hydraulique Mono Dimensionnel Par HEC RAS, Application Sur L’oued Aggay (Ville De Sefrou) - Lahsaini, Meriam; Tabyaoui, Hassan (European Scientific Journal, ESJ, 2018)
The city of Sefrou, because of its geographical position, its cultural heritage and urban planning, than economically, is classified as one of the sites with a vulnerability particular to floods. Oued Aggay, the subject of this study, constitutes a danger potential because of the violence of its floods. In this perspective that comes this study that part of the creation and management of a spatial database on flood risk in the Sebou basin. It aims to spatialize the extent of the floods of Oued Aggay and propose solutions to protection the city of Sefrou against floods. The chosen approach goes through a hydrological study, the choice of profiles and the construction of onedimensional model from HEC RAS hydrology software. This study allowed us to simulate floods by statistical methods, identify flood zones and determine the different water levels in the flooded area for the Oued Aggay watershed.